Word- or root-derived? A semantic test for instrumental denominal verbs in Italian - Alice Suozzi; Anna Cardinaletti (Isogloss)
Denominal verbs, in spite of their name, can be derived from either a noun or a root. In non-morphologically transparent languages, only semantic cues help distinguish the two classes, i.e., the entailment of existence of the corresponding noun (Kiparsky 1982, 1997). In this work, we present a novel semantic test which is the first attempt at distinguishing noun-derived from root-derived Instrumental Denominal Verbs (IDV) on a purely semantic basis, overcoming the flaws observed in previous syntactic tests. By explicitly asking Italian native speakers to mention the instruments that can be used to perform the action denoted by the verb, we measured the entailment of existence through the number of instrument nouns produced and the frequency of production of the corresponding instrument noun. Our test also contained parasynthetic verbs, whose behavior was influenced by the interaction between their derivation process and their meaning.